Comparative Metabolomic Analysis of the Neuroprotective Effects of Scutellarin and Scutellarein against Ischemic Insult - Tang, Hao; Tang, Yuping; Li, Nian-Guang; Lin, Hang; Li, Weixia; Shi, Qianping; Zhang, Wei; Zhang, Pengxuan; Dong, Zexi; Shen, Minzhe; Gu, Ting; Duan, Jin-Ao (PLOS ONE, 2015)
For more than thirty years, scutellarin (Scu) has been used in China to clinically treat acute cerebral infarction and paralysis. Scutellarein (Scue), the major Scu metabolite in vivo, exhibits heightened neuroprotective effects when compared to Scu. To explore the neuroprotective role of these compounds, we performed ultra-high-performance liquid chromatography-quadrupole/time-of-flight mass spectrometry (UHPLC-QTOF/MS) coupled with a pattern recognition approach to investigate metabolomic differences in a rat model of ischemia after treatment with each compound. We examined metabolites in urine, hippocampal tissue, and plasma, and we tentatively identified 23 endogenous metabolites whose levels differed significantly between sham-operated and model groups. Upon pathway analysis, we found an additional 11 metabolic pathways in urine, 14 metabolic pathways in the hippocampal tissue, and 3 metabolic pathways in plasma. These endogenous metabolites were mainly involved in sphingolipid metabolism, lysine biosynthesis, and alanine, aspartate, and glutamate metabolism. We found that metabolic changes after ischemic injury returned to near-normal levels after Scue intervention, unlike Scu treatment, further validating the heightened protective effects exerted by Scue compared to Scu. These results demonstrate that Scue is a potential drug for treatment of ischemic insult.